Revising Our Concepts about Stoma Covering a Low Rectal Anastomosis - Lotfy, Wael E.; Abdel Fattah, Ahmed Raafat; Eltih, Osama A.; Wasef, Peter H.; Ashour, Hassan R. (Journal of Coloproctology, 2021)
Introduction There has been conclusive evidence that defunctioning stoma with either transverse colostomy or ileostomy mitigates the serious consequences of anastomotic leakage. However, whether transverse colostomy or ileostomy is preferred for defunctioning a rectal anastomosis remains controversial. The present study was designed to identify the best defunctioning stoma for colorectal anastomosis.Objective To improve the quality of life in patients with rectal resection and anastomosis and reduce the morbidity before and after closure of the stoma.Patients and Methods The present study included 48 patients with elective colorectal resection who were randomly arranged into 2 equal groups, with 24 patients each. Group I consisted of patients who underwent ileostomy, and group II consisted of patients who underwent colostomy as a defunctioning stoma for a low rectal anastomosis. All surviving patients were readmitted to have their stoma closed and were followed-up for 6 months after closure of their stomas. All data regarding local and general complications of construction and closure of the stoma of the two groups were recorded and blotted against each other to clarify the most safe and tolerable procedure.Results We found that all nutritional deficiencies, dehydration, electrolytes imbalance, peristomal dermatitis, and frequent change of appliances are statistically more common in the ileostomy group, while stomal retraction and wound infection after closure of the stoma were statistically more common in the colostomy group. There were no statistically significant differences regarding the total hospital stay and mortality between the two groups.Conclusion and Recommendation Ileostomy has much higher morbidities than colostomy and it also has a potential risk of mortality; therefore, we recommend colostomy as the ideal method for defunctioning a distal colorectal anastomosis.
Keywords: low rectal anastomosis'; defunctioning stoma; ileostomy; colostomy